Quality of YouTube video resources on total knee arthroplasty: a search in Turkish - Kocaoğlu, Hakan; Merter, Abdullah; Karaca, Mustafa Onur; Özbek, Emre Anıl (The European Research Journal, 2021)
Objectives: We aim was to evaluate the quality and reliability of the information on knee arthroplasty available on YouTube in Turkish. Methods: A systematic search was conducted using the term “diz protezi” (knee prosthesis) on 1 June 2020.Videos were filtered based on their degree of relevance alone. Videos that were not in Turkish, not on knee prosthesis or without audio and/or image were excluded. Copied videos were evaluated as a single video. The first 50 videos that came up in the search were included in the study. Video quality was scored using Global Quality Score (GQS). To assess reliability, modified DISCERN scale was used. Results: The mean view count per video was 31.533 ± 100.921 and the total view count was 1.576.633. The mean duration per video was 337 ± 475 seconds. The median number of likes per video was 13 (0-426). The median number of dislikes per video was 2.5 (0-83). The mean GQS of the videos was 3.25 ± 0.9. When the reliability of the sources was evaluated using DISCERN, the mean score of the videos was 2.18 ± 1.2. It is striking that all videos were prepared by an orthopedic surgeon. Of the medical doctors preparing the resources, 44% had academic titles. Conclusions: It was found that Turkish resources on arthroplasty on YouTube are promising in terms of quality. Content creators must make effort to increase their reliability according to DISCERN.